Solution Mapping Tools: Identifying a Bottom-Up Approach to Social Innovation - Raditya Ardianto Taepoer; Kenta Ono; Prananda Luffiansyah Malasan; Meirina Triharini; Arianti Ayu Puspita; Intan Prameswari; Yulia Sugandi (Fakultas Seni Rupa dan Desain ITB, 2023)
A bottom-up approach to social innovation arises from the issues at the root of the innovation, which usually originates in the lower middle class. An essential approach to design for social innovation is to manage projects with identifiable organizational stakeholders considering relationships in the context of power holders and empowering socially vulnerable and marginalized communities. In local contexts, community participation processes can support grassroots movements toward sustainable systems where the focus is on more complex situations. For a better understanding, the Solution Mapping Tool is explored in this paper through a case study of a workshop held in the least-developed region of Indonesia. The workshop focused on inventing a bamboo distillation device for Moke, a traditional alcoholic beverage made from fermented palm fruits. Using the Solution Mapping Tools, learners were inspired to explore and discover the diverse solutions that communities use and generate daily. The tool helps everyday solutions become visible and identifiable regarding needs, assets, problems and challenges, benefits, and opportunities for the future. The Solution Mapping Tools can also increase learners’ empathy towards people, including communities, by providing a place to learn about their daily lives, experiential knowledge, and context. This paper extends existing publications on distributing and learning about local assets as a pre-design process before applying a participatory-based approach.